Насіннєва репродукція декоративних видів родини ранникових (Scrophulariaceae Juss.) в умовах Центрального Лісостепу України - Prokopchuk, V.М. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
According to the research reproduction peculiarities of the introductive Scrophulariaceae Juss. family plants, taking into consideration their cultivation into the Central Forest-Steppe of Ukraine, terms and duration of blooming of the 16 ornamental types with male reproductive cell vitality and seed productivity have been stated. As a result of the experimental studies on the efficiency of male and female plant organs functions in certain conditions, indices of the reproductive success of some plant types in the mentioned territory and the contribution of female and male component parts into the process of the seed formation have been stated. A certain component, which plays a role of a critical factor among the plant types with low seed productivity, has been investigated in this work.